Business-government nexus: the special case of Hong Kong. Issue 4 (3rd October 2016) - Cheng, Joseph
Abstract : Purpose: The purpose of this paper is to examine the business-government nexus in Hong Kong as a special case, thereby contributing to a comparative examination of various significant variables affecting the study of political and economic developments in East Asia. Design/methodology/approach: The paper considers the privileged position afforded to the major business groups in Hong Kong's political system as part of the pro-Beijing United Front. It adopts a historical perspective, relying on existing literature including media reports. As the author is both an academic and a long-term pro-democracy activist, his actual experiences and extensive interviews with various important participants in Hong Kong's business and political communities offer valuable perspectives. Findings: In the past, the business-government nexus was perceived to be a positive factor that contributed to the territory's economic growth. In the past decade or so, though, increasing dissatisfaction with the Hong Kong government's performance and the widening gap between the rich and the poor have led to the emergence of a legitimacy deficit on the part of the government, resulting in rising demands for democracy which have not been met. Divisions on these issues within the local business community have posed a severe challenge to the continuation of the business-government nexus. Originality/value: The author's actual experiences and his interviews with other participants in Hong Kong's politics provide observations of significant value. The Occupy Central campaign, which took off in the territory in 2014, demands serious consideration in terms of its political development and a key element for consideration is the response of the business-government nexus to it.